What works, who works? The impact of active labour market programmes on the employment prospects of young people in Ireland - Philip J. O'Connell; Fran MacGinnity (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
The international literature on active labour market programmes has generated inconsistent and confusing, but generally pessimistic, conclusions regarding their impact on the employment prospects of participants. This paper argues that much of this confusion is due to a general lack of attention to qualitative differences between programmes. The paper develops a typology of active labour market programmes, differentiating between training and employment measures on the basis of their orientation to the labour market and argues that programmes with a strong orientation to the market are more likely to improve the job prospects of participants than those characterised by weak market linkages. That hypothesis is tested using the results of a survey of young participants in labour market programmes in Ireland. The analysis shows that programmes with strong linkages to the labour market both enhance the employment prospects of their participants and increase their earnings, even when we take account of relevant individual characteristics such as education and previous labour market experience. – – Die internationale Literatur hat bisher inkonsistente und verwirrende, aber in der Regel pessimistische Schlußfolgerungen hinsichtlich der Beschäftigungswirkung für Teilnehmer in arbeitsmarktpolitischen Maßnahmen gezogen. In diesem Beitrag wird argumentiert, daß ein Großteil dieser Konfusion darauf zurückzuführen ist, daß den qualitativen Differenzen von Maßnahmen zu wenig Aufmerksamkeit geschenkt wurde. Es wird daher eine Typologie aktiver Arbeitsmarktpolitik entwickelt, bei der die Weiterbildungs- und Beschäftigungsmaßnahmen nach ihren Marktbezügen unterschieden werden. Maßnahmen, die sich an den Bedürfnissen des Marktes orientieren, verbessern die Beschäftigungsperspektiven der Teilnehmer deutlich mehr als Maßnahmen mit schwacher Marktorientierung. Diese These wird - unter Verwendung von Kontrollgruppen - durch eine ökonometrische Analyse von jungen Teilnehmern in Arbeitsmarktmaßnahmen in Irland getestet und bestätigt: Maßnahmen mit starker Marktorientierung erhöhen sowohl die Beschäftigungschancen als auch die Löhne der Teilnehmer, selbst wenn man die relevanten individuellen Merkmale wie Bildung und Arbeitsmarkterfahrung in Betracht zieht.
Keywords: 330